A review of the genus Syrastrenopsis Grünberg, 1914 (Lepidoptera, Lasiocampidae) - Zolotuhin, Vadim V.; Saldaitis, Aidas (Zootaxa, 2014)
The genus Syrastrenopsis Grünberg, 1914 is revised and two new species, S. panga Zolotuhin & Saldaitis, sp. nov. and S. hun Zolotuhin & Saldaitis, sp. nov. are described from North Sichuan and Shaanxi Provinces of China, respectively. All species of the genus are illustrated including the male of S. imperiatus Zolotuhin, 2001 which is described for the first time.